41st Annual North American Meeting of the Society for Medical Decision Making; October 21, 2019; Portland, Oregon Keynote Address The More Who Die, the Less We Care: Confronting the Deadly Arithmetic of Compassion*. (May 2020) - Slovic, Paul
In this keynote address delivered at the 41st Annual North American Meeting of the Society for Medical Decision Making, I discuss the psychology behind valuing human lives. Research confirms what we experience in our daily lives. We are inconsistent and sometimes incoherent in our valuation of human life. We value individual lives greatly, but these lives lose their value when they become part of a larger crisis. As a result, we do too little to protect human lives in the face of catastrophic threats from violence, natural disasters, and other causes. In medicine, this may pose difficult choices when treating individual patients with expensive therapies that keep hope alive but are not cost-effective for the population, for example, with end of life. Lifesaving judgments and decisions are highly context-dependent, subject to many forms of response mode and framing effects and affective biases. This has implications for risk communication and the concept of shared decision making. Slower, more introspective decision making may reduce some of the biases associated with fast, intuitive decisions. But slow thinking can also introduce serious biases. Understanding the strengths and weaknesses of fast and slow thinking is a necessary first step toward valuing lives humanely and improving decisions.